2015
DOI: 10.1007/s10479-015-1954-x
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Indonesian fuel subsidy reform: a social accounting matrix analysis

Abstract: The debate over phasing out fuel subsidies in Indonesia is quite intense. Recent studies pointed out an unfair distribution of subsidies. Besides this, the burden of fuel subsidies to Indonesian government is expected to increasingly continue in parallel with rising fuel consumption as well as international oil prices. However, recent experiences indicated that phasing out the fuel subsidy could potentially result in adverse effects in the economy. Then, the need for comprehensive economy-wide analyses in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The government regulates the fuel price. This condition leads to fiscal pressure because of an increase in fuel subsidies [25]. In the context of EVs transition, due to its market size and fuel subsidies, Indonesia has the potential to adopt EVs technology in the future transportation sector.…”
Section: Sector Conditionmentioning
confidence: 99%
“…The government regulates the fuel price. This condition leads to fiscal pressure because of an increase in fuel subsidies [25]. In the context of EVs transition, due to its market size and fuel subsidies, Indonesia has the potential to adopt EVs technology in the future transportation sector.…”
Section: Sector Conditionmentioning
confidence: 99%
“…Dartanto (2013) examined the relationship between existing fuel subsidies and fiscal balance in Indonesia between 1998 and 2013 and found that removing 25 percent of fuel subsidies increased poverty by 0.259 percentage points while 100 percent removal of fuel subsidies and the reallocation of 50 percent of them to government spending decreased poverty by 0.277 percentage points. Fathurrahman et al (2017) showed that the reallocation of subsidy payments to low-income households could slow down economic development but improve social welfare. However, removing fuel subsidy usually comes with the promise of using the money saved from subsidy to undertake targeted reform.…”
Section: Related Literaturementioning
confidence: 99%
“…In addition to efficiency improvements, removing fossil fuel subsidies may encourage innovation and modernization, which make the firms more competitive 53 . Removing energy subsidies and reallocating a certain proportion of them to economic sectors reduces total emissions besides an improvement in energy efficiency 54 . However, reallocation of a share of these subsidies to renewable energies not only improves the economic performance and socioeconomic welfare, both in the short and long runs, but also helps to optimize the energy system by making the energy consumption structure cleaner, improving energy efficiency, and addressing the problem of imbalanced distribution and consumption of energy 55–59 .…”
Section: Review Of Literaturementioning
confidence: 99%